The East India Company at home, 1757-1857 - Finn, Margot C.; Smith, Kate, 1981- (London : UCL Press, 2018)
The East India Company at Home, 1757?1857' explores how empire in Asia shaped British country houses, their interiors and the lives of their residents. It includes chapters from researchers based in a wide range of settings such as archives and libraries, museums, heritage organisations, the community of family historians and universities. It moves beyond conventional academic narratives and makes an important contribution to ongoing debates around how empire impacted Britain.
Includes bibliographical references (pages 433-504) and index.
Keywords: East India Company -- Influence; Interior decoration -- Great Britain -- History -- 19th century